Developing an integrated biosocial theory to understand juvenile delinquency: from the social, cognitive, affective, and moral (SCAM) perspectives - Du, Yu (International Journal of Contemporary Pediatrics, 2019)
Biosocial theory has made considerable progress in explaining juvenile delinquency and making explicit references for juvenile justice policy during the past decades. However, because biosocial theory aims to identify multiple risk factors, it makes juvenile justice practice and develop delinquency prevention programs difficult. This paper proposes an integrated biosocial theory from the social, cognitive, affective, and moral (SCAM) perspectives to understand juvenile delinquency and facilitate the development and improvement of prevention and intervention programs. The article briefly summarizes the background and the key concepts of the chosen criminological theories and the logic of theoretical integration. Then it articulates the four aspects of the integrated biosocial theory and how it can contribute to criminology in details. Lastly, the paper identifies its potential limitations and provides practical implications.